2016
DOI: 10.1101/086991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent progress in multi-electrode spike sorting methods

Abstract: In recent years, arrays of extracellular electrodes have been developed and manufactured to record simultaneously from hundreds of electrodes packed with a high density. These recordings should allow neuroscientists to reconstruct the individual activity of the neurons spiking in the vicinity of these electrodes, with the help of signal processing algorithms. Algorithms need to solve a source separation problem, also known as spike sorting. However, these new devices challenge the classical way to do spike sor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The proposed method with different strategies to estimate the number of neurons as shown in II-C2 is compared. Since the existing literatures [44], [45] have reported that the maximal number of neurons detected by extracellular electrodes is between 8 and 10, an initial range of the estimated number of neurons is set between 2 and 10 in this paper. The reduced dimension, m 0 , is assigned to 3 at the initialization stage in 5) 2( 4) 2( 5) 2(4) 2( 5) 4( 5) 2(4) our method.…”
Section: B Numerical Simulations On the Synthetic Datasetmentioning
confidence: 99%
“…The proposed method with different strategies to estimate the number of neurons as shown in II-C2 is compared. Since the existing literatures [44], [45] have reported that the maximal number of neurons detected by extracellular electrodes is between 8 and 10, an initial range of the estimated number of neurons is set between 2 and 10 in this paper. The reduced dimension, m 0 , is assigned to 3 at the initialization stage in 5) 2( 4) 2( 5) 2(4) 2( 5) 4( 5) 2(4) our method.…”
Section: B Numerical Simulations On the Synthetic Datasetmentioning
confidence: 99%
“…In addition, large amplitude spikes could potentially overshadow low-amplitude ones. Recent development of a new spike sorting algorithm for multi-electrode arrays has partially resolved the issues associated with temporally overlapping spikes, on the condition that these spike waveforms are sufficiently different on the detection electrode (Lefebvre et al, 2016;Pachitariu et al, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…These devices enable access to hundreds of neurons distributed across multiple brain regions, densely sampling the extracellular field; this means that each neuron is detected on multiple channels of a probe. This additional resolution in sampling is expected to aid analysis and is currently being used by novel algorithms [14][15][16][17] .…”
Section: Introduction Extracellular Recordingsmentioning
confidence: 99%